PENGARUH KOMPENSASI DAN PRODUKTIVITAS KERJA TERHADAP KINERJA PEGAWAI PERUSAHAAN AIR MINUM DAERAH (PDAM) KOTA SOLOK: THE INFLUENCE OF COMPENSATION AND WORK PRODUCTIVITY ON THE PERFORMANCE OF EMPLOYEES IN THE REGIONAL DRINKING WATER COMPANY (PDAM) OF SOLOK CITY - Damara, Devina; Yeni, Afni; Irawan, Hendri (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
ABSTRACT This research aims to determine the implementation of employee performance from compensation factors and work productivity with a sample of 63 respondents who were studied using quantitative methods. Based on the results of statistical analysis, it can be interpreted that compensation partially has a significant effect on employee performance, this is proven by the t test with a significant value of 2,000 > 2.30 in the significance level value, 0.000 < 2,000. So it can be interpreted that the development of compensation has a significant effect on employee performance. Based on the results of statistical analysis, it can be concluded that Work Productivity partially has a significant effect on Employee Performance. This is proven by the t test with a significant value of 2,301 > 2,000 and a significance level value of 0.025 < 0.05, so it can be concluded that Performance has a significant effect on Work Productivity. So it can be concluded that, Compensation and Work Productivity have a significant effect. This can be proven, so it can be concluded that Work Productivity was carried out using the f test with a calculated f significant value of 3.15 and 35.152 with the resulting significant value of 0.00. This can also be seen from the Rsquare obtained at 2,301. Keywords: Compensation,;Work Productivity;Employee Performance